Associations of IL17A G-197A single nucleotide polymorphism with immunological parameters and structural changes of the brain in schizophrenia - I. K. Malashenkova; V. L. Ushakov; S. A. Krynskiy; D. P. Ogurtsov; N. A. Khailov; A. Yu. Ratushnyy; E. A. Filippova; N. V. Zakharova; G. P. Kostyuk; N. A. Didkovsky (Медицинская иммунология, 2023)
Schizophrenia is a chronic mental disorder that is caused by a complex palette of genetic, epigenetic and environmental factors. Some of the important components of its pathogenesis are systemic inflammation and the dysfunction of immunity, which lead to neuroinflammation, contributing to development of structural brain changes. Earlier we have shown that increase in interleukin-17A levels is associated with morphometric changes and immune dysregulation in schizophrenia. IL17A G-197A (rs2275913) genetic polymorphism is involved in determining interleukin-17A secretion. The goal of this work was to investigate the associations between rs2275913 polymorphism, immune disorders and structural neurovisualization findings in schizophrenia to provide new insights into the immunopathogenesis of this disease. 60 patients aged 18 to 42 years diagnosed with schizophrenia were enrolled. 85 healthy volunteers were included into the control group. Multiplex assay was used to determine cytokine and chemokine serum levels. Rs2275913 polymorphism was assessed by polymerase chain reaction with electrophoretic detection of amplification products. A number of relationships between rs2275913 polymorphism and the immune parameters in schizophrenia were revealed. Carriers of G allele showed significant increase in IFNY, a key cytokine of Th1-link of adaptive immunity, and IL-8, an inflammatory chemokine. Also, increased levels of CXCL16 were observed in patients carrying the G allele. CXCL16 activates secretion of other proinflammatory chemokines and is involved in activation of Th1 adaptive immunity. Associations of heterozygous GA genotype with reduced cortical thickness in a number of areas of the frontal cortex in schizophrenia were found. Changes in cortical thickness in some of these areas, including middle frontal gyrus and orbitofrontal cortex, can be relevant to the pathogenesis of schizophrenia. The results highlight the importance of immunogenetic factors in the pathogenesis of schizophrenia and indicate that the rs2275913 polymorphism requires further studies as a potential biomarker of immune dysregulation and morphometric brain changes in schizophrenia.